Use of 99mTc in The Field of Radiofarmation: A Review - Faruk Jayanto Kelutur; Holis Abdul Holik (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Technetium-99m (99mTc) has been applied in nuclear medicine as a radiopharmacyfor both diagnosis and therapy. 99mTc is obtained from a 99Mo/99mTc (half-life 66 h) generator in the form of sodium pertechnetate (Na[99mTcO4]) by decaying to 99Tc for 6 hours and emitting gamma energy rays (Eɤ = 140 keV). This radionuclide has an electron configuration of 4d5 5s2, which will form complexes with different ligands and have oxidation rates from +1 to +7. The coordinated complex of technetium-99m has been utilized in nuclear medicine in tissues and organs (thyroid, red and white blood cells, kidneys, brain, myocardial, and bone). The resulting kit production must have based on Good Manufacturing Practice, which consists of batch planning, washing, sterilization of glassware and stopper, starting material, preparation of large quantities of the solution, sterile filtration, dispensing, crimping, a summary of process control, quarantine, packaging and leaving the production premises.